2018
DOI: 10.1029/2018gl078759
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Water Mass Transport of Legacy POPs in the Arctic Ocean

Abstract: The Arctic Ocean is known to be contaminated by various persistent organic pollutants (POPs). The Fram Strait, the only deepwater passage to the Arctic Ocean (from the Atlantic Ocean), represents an unquantified gateway for POPs fluxes into and out of the Arctic. Polyethylene passive samplers were deployed in vertical profiles in the Fram Strait and in air and surface water in the Canadian Archipelago to determine the concentrations, profiles, and mass fluxes of dissolved polychlorinated biphenyls (PCBs) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…We found that with the increase of PAH molecular weight, the net mass flux to the Arctic Ocean increased. Previous studies reveal similar trends for PFAS, as a net outflow for shorter‐chain PFASs and HCHs, while a net inflow for the PFASs with ≥eight perfluorinated carbons or high‐molecule‐weighted PCBs (Joerss et al., 2020; Y. Ma et al., 2018).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…We found that with the increase of PAH molecular weight, the net mass flux to the Arctic Ocean increased. Previous studies reveal similar trends for PFAS, as a net outflow for shorter‐chain PFASs and HCHs, while a net inflow for the PFASs with ≥eight perfluorinated carbons or high‐molecule‐weighted PCBs (Joerss et al., 2020; Y. Ma et al., 2018).…”
Section: Resultsmentioning
confidence: 57%
“…The Arctic Ocean, linking the Atlantic Ocean and the Pacific Ocean, is a fundamental node in the global hydrological cycle and thermohaline circulation (Carmack et al., 2016; Talley et al., 2011). A major inflow to the Arctic Ocean comes from the Atlantic through the Fram Strait and the Barents Sea, with a minor inflow from the Pacific side through Bering Strait (Liu, Chen, et al., 2021; Y. Ma et al., 2018). The outflow from the Arctic Ocean, being cold and fresh, is mainly conveyed by East Greenland Current through the Fram Strait, which is the only deep channel allowing energy and materials to exchange between the Arctic Ocean and other oceans (X. Wang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Depth profiles of PFASs in this study were different from those of more hydrophobic legacy POPs such as polychlorinated biphenyls (PCBs) and dichlorodiphenyltrichloroethanes (DDTs), for which highest concentrations in Fram Strait were not found in the upper water layers, but in intermediate or deep waters . This was expected because for hydrophobic POPs, which partition readily to organic carbon and suspended particles, particle settling is suggested to be a dominant transport pathway to deeper water layers (“biological pump”).…”
Section: Resultsmentioning
confidence: 99%
“…These compounds, which include hexachlorocyclohexanes (HCHs) and dichlorodiphenyltrichloroethanes (DDTs), have proved to be persistent and bioaccumulative in the environment, have the potential for long‐range atmospheric transport, and have proved to be toxic to wildlife and humans (Li et al, 1998; Stemmler & Lammel, 2009; Willett et al, 1998). Because of their ecological and health risks, these pesticides started to be phased out globally apart from specific uses such as DDT for malaria vector control, and they have been added to the Persistent Organic Pollutants (POPs) list of the Stockholm Convention (Cai et al, 2010; Li et al, 2017; Ma et al, 2018). Legacy OCPs have been detected globally in atmospheric, aquatic, and geological systems and in remote regions such as the Himalayas and polar regions (Bailey et al, 2000; Cai et al, 2012; Gao et al, 2010; Huang et al, 2013; Li, 1999; Ren et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ocean currents passing through the Bering Strait make a significant contribution to the input of OCPs to the Arctic Ocean, particularly for β‐hexachlorocyclohexane (β‐HCH) (Li et al, 2002). River runoff carries land‐based OCPs from soils, dry or wet absorption, and snow and ice meltwater into the large Arctic drainage basin, which arguably is mostly the result of prior LRAT (Cai et al, 2012; Lambert et al, 2019; Ma et al, 2018). OCPs from atmospheric, oceanic, and riverine sources thus converge in the Arctic Ocean (Bidleman et al, 2015; Cabrerizo et al, 2018; Hung et al, 2016), with Arctic regions acting as reserves and secondary sources of OCPs (Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%